Transport and distribution made simple - Benson, Don S.; Whitehead, Geoffrey (London : W. H. Allen, 1975)
This book introduces the reader to the whole field of transport and physical distribution, as practiced in the 1970s. The book will prepare the reader for a wide range of examination syllabuses of the Chartered Institute of Transport and the Institute of Traffic Administration.
Includes bibliographical references and index.
osa 29/01/2019
Loans
Keywords: Shipment of goods; Physical distribution of goods; Transportation